A normative study of acronyms and acronym naming - Cristina Izura (Behavior Research Methods, 2012)
Acronyms are an idiosyncratic part of our everydayvocabulary. Research in word processing has used acronymsas a tool to answer fundamental questions such as thenature of the word superiority effect (WSE) or which is thebest way to account for word-reading processes. In thisstudy, acronym naming was assessed by looking at theinfluence that a number of variables known to affect mainstreamword processing has had in acronym naming. Thenature of the effect of these factors on acronym naming wasexamined using a multilevel regression analysis. First, 146acronyms were described in terms of their age of acquisition,bigram and trigram frequencies, imageability, numberof orthographic neighbors, frequency, orthographic and phonologicallength, print-to-pronunciation patterns, and voicingcharacteristics. Naming times were influenced by lexical andsublexical factors, indicating that acronym naming is a complexprocess affected by more variables than those previouslyconsidered.